Effectiveness of 5% Channa Striata Extract Gel in Wound Healing: A Double-blind Randomized Controlled Trial - Yahya, Yulia Farida; Kurniawati, Yuli; Bahar, Erial; Toruan, Theresia Lumban; Kartowigno, Soenarto; Purwoko, Muhammad Izazi Hari; Octyvani, Tiar Marina (UI Scholars Hub, 2025)
Background: Snakehead fish (Channa striata, CS) has traditionally been used in Indonesia as a nutrient to promote wound healing. It contains protein highly similar to human protein, which may be involved in wound healing via biological pathways. We aim to determine the effectiveness of the topical 5% CS extract gel in promoting wound healing. Methods: A double-blind, placebo-controlled randomized clinical trial was conducted from June to August 2022 at the Department of Dermatology, Venereology, and Aesthetics of Dr. Mohammad Hoesin Hospital. We allocated 32 post-skin surgery participants with grade I acute superficial wounds on the face, neck, trunk, and extremities into 2 groups with one receiving 5% CS (n=16) and the other receiving placebo (n=16). Both groups applied the treatments twice daily. Assessments of wound healing using modified REEDA (redness, edema, ecchymosis, drainage, approximation) score, wound size, and adverse effects were done at follow-up days 1, 3, and 7. Results: Both groups showed REEDA score improvements on days 1, 3, and 7, with significant difference between both groups identified on day 3 (p=0.038). Wound size improved at each follow-up in all participants, with the 5% CS group being slightly better than the placebo group on day 3 (p>0.05). A mild adverse event was found in only one participant in the 5% CS group (3.1%). Conclusion: Both 5% CS extract gel and placebo had good safety profile and were effective in promoting wound healing. 5% CS extract gel was better at reducing REEDA score.